Monólogos y Polifonía en Tiempo de silencio de Luis Martin Santos - Khalida TOUIL (Altralang Journal, 2019)
ABSTRACT: Our article entitled "The Polyphony in the Monologues of Tiempo de Silence by Luis Martin Santos" aims at the descriptive analysis of the phenomenon of polyphony in monologues, on the one hand, and the way in which this polyphony is constitutive of the literalism of another.